26. 13x2=26.
(x - 2)(x + 2)(x - 3)(x + 3)
No. If I said 13x2, that would be 26. Then +5 equals 31, so no.
5
2x^3 - 3x^2 + 4x - 3
13x2
26. 13x2=26.
26
x3 + 13x2 + 42x = x(x + 6)(x + 7).
13x2 2x13
13X2
36x1 13x2 12x3 9x4 6x6
no. it can be simplified into 13x2. 13 and 2 are prime.
-x2(5x5 + 13)
13x1=13 13x2=26...etc
x3+13x2=-22xadd 22x to both sides:x3+13x2+22x=0now factor:x(x2+13x+22)=0x(x+11)(x+2)=0x=0x+11=0x+2=0Therefore the solution to this equation is x=0, x=-11, x=-2
the answer is 13x2=26 posted by a genius